2013
DOI: 10.1200/jco.2013.31.4_suppl.398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of KRAS mutation on recurrence patterns in patients undergoing hepatic resection of colorectal metastases.

Abstract: 398 Background: There have been conflicting results about whether KRAS mutation influences outcome in patients (pts) with colorectal cancer. In pts who underwent liver resection, Karagkounis reported a worse recurrence and survival in KRAS mutated (MUT) patients (ASCO 2012, abs 3616). Methods: In 105 pts who underwent liver resection and received adjuvant (adj) hepatic arterial infusion and systemic chemotherapy and in whom KRAS data was available, we evaluated recurrence patterns and survival. Correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
98
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(111 citation statements)
references
References 0 publications
10
98
3
Order By: Relevance
“…This interpretation is consistent with the evidence that the percentage of KRAS mutated patients ranged from 14% (Stremitzer et al, 2012) to 37% (Teng et al, 2012) in all seven included studies, compared to 35-45% reported in metastatic and unresectable CRC, suggesting a significant association between KRAS mutations rates and tumor behavior, as described in preclinical studies (Suchy et al, 1992;Tanaka et al, 1994;Varghese et al, 2002;Webb et al, 1998). Some clinical series have also shown that KRAS mutations are associated with an increased risk of developing lung and liver metastases compared to wild-type population (Vauthey et al, 2013;Kemeny et al, 2014). Others have shown a higher incidence of lung metastases/recurrence than liver metastases/recurrence in KRAS mutated patients (Vauthey et al, 2013;Tie et al, 2011;Kim et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…This interpretation is consistent with the evidence that the percentage of KRAS mutated patients ranged from 14% (Stremitzer et al, 2012) to 37% (Teng et al, 2012) in all seven included studies, compared to 35-45% reported in metastatic and unresectable CRC, suggesting a significant association between KRAS mutations rates and tumor behavior, as described in preclinical studies (Suchy et al, 1992;Tanaka et al, 1994;Varghese et al, 2002;Webb et al, 1998). Some clinical series have also shown that KRAS mutations are associated with an increased risk of developing lung and liver metastases compared to wild-type population (Vauthey et al, 2013;Kemeny et al, 2014). Others have shown a higher incidence of lung metastases/recurrence than liver metastases/recurrence in KRAS mutated patients (Vauthey et al, 2013;Tie et al, 2011;Kim et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…1). Three of these studies were retrospective series (Vauthey et al, 2013;Kemeny et al, 2014;Francesca Bergamo and Loupakis et al, 2014), while the others were prospective studies (Nash et al, 2010;Karagkounis et al, 2013;Stremitzer et al, 2012;Teng et al, 2012). In these 7 studies, sample sizes of the analyzed population ranged from 60 (Stremitzer et al, 2012) to 309 (Schirripa et al, 2015), while the percentage of KRAS mutated patients ranged from 14% (Stremitzer et al, 2012) to 37% (Teng et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations